Policy and institutional arrangements to enhance water use efficiency in irrigated agricultture in Vietnam - Le, Van Chinh (2021)
This paper assesses of policy and institutional aspects for water use efficiency in irrigated agriculture, focusing on the recent law on hydraulics works, and policies on canal lining and water saving irrigation in 14 provinces in Vietnam. It points out that thanks to these policies results of canal lining and advanced irrigation are considerable. In fact, more than hundred thousand hectares of crops was irrigated with advanced and water saving technologies and about 40% of irrigation canal was lined. This significantly contributes to improving water use efficiency in irrigation sector. However, there are various factors influencing these policies and the law leading to a number of issues and difficulties in implementation. Based on research results, several solutions to policy and institutional arrangements for enhancing water use efficiency in irrigated agriculture are recommended.